MTT-S International Microwave Symposium Digest
DOI: 10.1109/mwsym.1977.1124403
|View full text |Cite
|
Sign up to set email alerts
|

A Low Noise MIC GaAsFET Amplifier for 4 GHz Radio

Abstract: A low noise amplifier for 4 GHz radio has been designed and is in manufacture. The noise figure is < 2 dB and the gain is typically 10 d!d. Input and output return losses are > 25 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The stability factor KT and the maximum available gain GT of feedback structure are given by [3]. By controlling the feedback parameters YV., a feedback network can be found that makes the device unconditionaliy stable (KT > 1), obtaining a gain given by (2), and lowering the S and ST2 parameters. In a recent and more extensive paper [4] we have described in detail a graphical method to obtain the required YVj parameters.…”
Section: Basic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The stability factor KT and the maximum available gain GT of feedback structure are given by [3]. By controlling the feedback parameters YV., a feedback network can be found that makes the device unconditionaliy stable (KT > 1), obtaining a gain given by (2), and lowering the S and ST2 parameters. In a recent and more extensive paper [4] we have described in detail a graphical method to obtain the required YVj parameters.…”
Section: Basic Theorymentioning
confidence: 99%
“…This makes useless the concepts of finite maximum available gain and simultaneous conjugate matching. Normal broadband design with this type of MESFET is difficult, requiring a lot of computer work or using balanced configurations or the insertion of isolators [1], [2].…”
Section: Introductionmentioning
confidence: 99%